Efikasi Diri Pada Remaja Ditinjau Dari Religiusitas - Umi Nur Holifah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine whether there is a relationship between religiosity with self-efficacy in late adolescents, this study uses quantitative research. The sample in this study amounted to 98 people from the Study Program Sufism and Psychotherapy of UIN Raden Fatah Palembang determined by purposive sampling technique and based on Piaget’s opinion. The data collection method uses a Likert Scale consisting of the religiosity scale and self-efficacy scale. The method of analyzing research data uses product moment analysis. The findings in this study are that there is a very significant relationship between religiosity and self-efficacy in late adolescents. In the sense that individual religiosity can affect the level of individualself-efficacy